Influence of delayed placement and dietary lysine levels on small intestine morphometrics and performance of broilers - JRG Franco; AE Murakami; MRM Natali; ERM Garcia; AC Furlan (Brazilian Journal of Poultry Science, 2006)
This experiment studied the influence of delayed placement (HI) and digestible lysine level (DL) on the morphometrics of the intestinal mucosa and on the performance of broilers. A total number of 1,705 Cobb 500 male chicks were used in a completely randomized experimental design in a factorial arrangement with four HI (12, 24, 36 and 48h), and two DL level in the starter diet (1.143 and 1.267%), with four replicates and 55 birds per experimental unit. The amino acids methionine-cystine, threonine, and tryptophan were balanced according to the ideal protein (IP) concept. Small intestine morphometrics was evaluated using histology slides of the duodenum and jejunum. There was no interaction between HI and DL levels for any of the studied parameters. The 1.143% level of DL promoted better performance results at 21 and 42 days of age, as well as higher duodenum and jejunum crypt depth, and duodenum villi height at 21 days of age. HI negatively influenced the morphometrics of the small intestine during the starter phase, and the performance of broilers up to 42 days of age. There was no effect of the treatments on yolk sac utilization or abdominal fat percentage. It was concluded that the use of 1.143% DL and HI of 12 hours promoted better development of the small intestine mucosa up to 21 days of age, and broiler performance at market age.